ChemInform Abstract: Stereocontrolled Cyanohydrin Ether Synthesis Through Chiral Broensted Acid‐Mediated Vinyl Ether Hydrocyanation. Issue 9 (4th March 2014) - Lu, Chunliang; Su, Xiaoge; Floreancig, Paul E.
Abstract It is found that vinyl ethers can smoothly be converted into cyanohydrin ethers.